2016
DOI: 10.1186/s12879-016-1971-7
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial infection of CCHF among health care workers in Rajasthan, India

Abstract: BackgroundEver since Crimean-Congo hemorrhagic fever [CCHF] discovered in India, several outbreaks of this disease have been recorded in Gujarat State, India. During the year 2011 to 2015 several districts of Gujarat and Rajasthan state (Sirohi) found to be affected with CCHF including the positivity among ticks and livestock. During these years many infected individuals succumbed to this disease; which subsequently led to nosocomial infections. Herein, we report CCHF cases recorded from Rajasthan state during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…The infection can also be acquired through direct contact with blood and other bodily fluids from infected animals and humans, mainly those with a high viral load, including hospitalized patients with hemorrhagic fever. Thus, there is a high risk of transmission in healthcare environments [8,[12][13][14]. Currently, the CCHF virus (CCHFV) is considered a level 4 biosecurity risk pathogen by the Centers for Disease Control and Prevention (CDC) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The infection can also be acquired through direct contact with blood and other bodily fluids from infected animals and humans, mainly those with a high viral load, including hospitalized patients with hemorrhagic fever. Thus, there is a high risk of transmission in healthcare environments [8,[12][13][14]. Currently, the CCHF virus (CCHFV) is considered a level 4 biosecurity risk pathogen by the Centers for Disease Control and Prevention (CDC) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Transmission to humans occurs as a result of bites from infected ticks or via exposure to body fluids from viremic animals or humans [3]. Therefore, nosocomial transmission to healthcare workers is an important concern [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There are scanty reports on the ability of this species to transmit diseases in both humans and animal. However, it is a known vector agent of the protozoan Babesia bigemina, Crimean-Congo hemorrhagic fever virus (CCHFV), and Ehrlichia ruminantium [55][56][57]. Mediannikov et al [54] has reported on the ability of R. evertsi evertsi to transmit rickettsial agents in ticks that were collected in Senegal.…”
Section: Discussionmentioning
confidence: 99%